Flood forecasting on the Tocantins River using ensemble rainfall forecasts and real‐time satellite rainfall estimates. Issue 3 (5th June 2015) - Fan, F.M.; Collischonn, W.; Quiroz, K.J.; Sorribas, M.V.; Buarque, D.C.; Siqueira, V.A.
Abstract: The Tocantins River, located at the northern region of Brazil with over 300 000 km 2 of drainage area, is an important water body in terms of hydropower production. The occurrence of floods along the Tocantins River is a relatively frequent event that affects hydropower plant operations and several cities and their inhabitants. Motivated by recent flooding issues, a hydrological forecasting system was developed in order to assist the decision making of dam operation for flood control. The model uses merged rainfall information from ground‐based telemetric gauges and real‐time TRMM satellite rainfall estimates. Streamflow forecasts are obtained based on quantitative precipitation forecasts from two different sources, CPTEC Eta 15 km regional deterministic model and the Global Ensemble Forecasting System‐VII, maintained by the National Center for Environmental Prediction‐National Oceanic and Atmospheric Administration. We present here the forecasting system analysis of the 2011/2012 rainy season flood predictions with the use of ensemble forecasts, and comparison results of deterministic and ensemble forecasts for the major flood of 2012/2013.